Comprehending and Confronting Antisemitism - Lange, Armin; Porat, Dina; Schiffman, Lawrence H.; Mayerhofer, Kerstin (An End to Antisemitism!, 2020)
This volume provides a compendium of the history of and discourse about antisemitism - both as a unique cultural and religious category. Antisemitic stereotypes function as religious symbols that express and transmit a belief system of Jew-hatred, which are stored in the cultural and religious memories of the Western and Muslim worlds, migrating freely between Christian, Muslim and other religious symbolic systems.